2012
DOI: 10.5539/gjhs.v5n1p107
|View full text |Cite
|
Sign up to set email alerts
|

Is vitamin D deficiency associated with non specific musculoskeletal pain?

Abstract: Backgrounds:Vitamin D deficiency is common worldwide, including Iran. It has been suggested that vitamin D deficiency is associated with non-specific musculoskeletal pain. The aim of this study is evaluation of the association of musculoskeletal pain with vitamin D deficiency and the response of the patients to vitamin D supplementation.Materials and Methods:sixty two adult patients with chief complaint of musculoskeletal pain were enrolled in the study. Serum concentrations of 25(OH)D, Calcium, Phosphate, Alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 19 publications
2
31
0
1
Order By: Relevance
“…A higher prevalence rate of vitamin D deficiency was reported among populations with musculoskeletal and/or widespread pain conditions. Some studies showed high prevalences of suboptimal vitamin D levels in populations with musculoskeletal and/or widespread pain conditions 98–101…”
Section: Discussionmentioning
confidence: 99%
“…A higher prevalence rate of vitamin D deficiency was reported among populations with musculoskeletal and/or widespread pain conditions. Some studies showed high prevalences of suboptimal vitamin D levels in populations with musculoskeletal and/or widespread pain conditions 98–101…”
Section: Discussionmentioning
confidence: 99%
“…Also, more improvement was reported in old patients with back pain who received vitamin D in comparison to the placebo . Abbasi and coworkers reported more than 60% decrease of VAS score in a majority of patients with musculoskeletal pain and vitamin D deficiency when treated with oral vitamin D 3 . However, two recent meta‐analyses by Straube revealed contrasting outcomes between results of randomized clinical trials (RCTs) and other study designs.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to other investigations, the obvious difference in the present study is the lower mean age of the patients. Similar to the study by Warner and coworkers, in the current study, the outcome was “decrease of pain VAS score.” However, in some studies showing a good effect of vitamin D 3 in alleviating chronic pain, the outcome was expressed as “percentage of patients with improvement of pain.” Therefore, the methodology of reporting the outcome may be a contributing factor to the evaluation of the effectiveness of vitamin D in chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En el grupo que si respondió al tratamiento los niveles de VD alcanzados fueron de 60.6 ± 27.6 comparados con 39.2 ± 9.6 nmol/l p<0.01 en los que no. Concluyen que el tratamiento con VD mejora el dolor en la mayoría de los pacientes con deficiencia de esta vitamina y que la falta de respuesta puede ser por el aumento insuficiente de niveles séricos de VD, por lo cual recomiendan reevaluar los niveles en quienes no respondan 20 .…”
Section: Evidencia a Favorunclassified